Population pharmacokinetic model linking plasma and peripheral blood mononuclear cell concentrations of efavirenz and its metabolite, 8-hydroxy-efavirenz, in HIV Patients - Habtewold, Abiy; Aklillu, Eleni; Burhenne, Jürgen (Antimicrobial agents and chemotherapy, 2017)
The objectives of this study were to characterize the population pharmacokinetics (PK) of efavirenz (EFV) and 8-hydroxy-efavirenz (8OHEFV) in plasma and peripheral blood mononuclear cells (PBMCs) and to explore covariates affecting the PK parameters. Fifty-one patients had steady-state 0-to-24-h concentrations of EFV and 8OHEFV in plasma with corresponding concentrations in PBMCs, while 261 patients had one or two sparse concentrations at 16 ± 1 h postdose at weeks 4 and/or 16. The pharmacogenetic markers CYP2B6*6, CYP3A5*3, CYP3A5*6, UGT2B7*2, ABCB1 (3435C→T, 3842A→G), OATP1B1*1B, and OATP1B1*5, the presence of a rifampin-based antituberculosis (anti-TB) regimen, baseline body weight and organ function values, and demographic factors were explored as covariates. EFV concentration data were well described by a two-compartment model with first-order absorption (Ka) and absorption lag time (Alag) (Ka = 0.2 h−1; Alag = 0.83 h; central compartment clearance [CLc/F] for CYP2B6*1/*1 = 18 liters/h, for CYP2B6*1/*6 = 14 liters/h, and for CYP2B6*6/*6 = 8.6 liters/h) and PBMCs as a peripheral compartment. EFV transfer from plasma to PBMCs was first order (CLp/F = 32 liters/h), followed by capacity-limited return (Vmax = 4,400 ng/ml/h; Km = 710 ng/ml). Similarly, 8OHEFV displayed a first-order elimination and distribution to PBMCs, with a capacity-limited return to plasma. No covariate relationships resulted in a significant explanation of interindividual variability (IIV) on the estimated PK parameters of EFV and 8OHEFV, except for CYP2B6*6 genotypes, which were consistent with prior evidence. Both EFV and 8OHEFV accumulated to higher concentrations in PBMCs than in plasma and were well described by first-order input and Michaelis-Menten kinetics removal from PBMCs. CYP2B6*6 genotype polymorphisms were associated with decreased EFV and 8OHEFV clearance.
Gesehen am 18.09.2018